Fenomena Etika Agama dan Spiritualisasi Politik Perspektif Islam - M. Sidi Ritaudin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2009)
In this modern era, both in the West and East, it seems less tied to the religion and increasingly rely on the ratio as the key to solving life’s problem, Lately, the New Age Movement emerged as a critical reaction against the rational modernity. This movement believes that there is a fundamental change to the dominance of reason and science over God (read: faith). This movement is seeking a new balance between reason and faith are concentrated toward the inner roads of the divine source of life. Ironically, the diversity of emerging forms of spirituality in this world does not give positive effect toa number of politicians (representatives) in our country who would later carve it with a black smudge their actions contrary to ethics. This paper was trying to offer ideas about the need for political spirituality and political piety five roads to meet the spiritual needs of the community group.